Prevalence of genotype D in chronic liver disease patients with occult HBV infection in northern region of India - Meher Rizvi; Mohd Azam; Asfia Sultan; Indu Shukla; Abida Malik; Masihur Reman Ajmal; Fatima Khan; Hiba Sami (Wolters Kluwer Medknow Publications, 2014)
Background: Etiology of nearly 30% cases of chronic viral hepatitis remains undetected. Occult HBV infection (OBI) has emerged as an important clinical entity in this scenario. Apart from prevalence and clinical outcome of OBI patients genotype was determined in northern region of India. Materials and Methods: A total of 847 patients with chronic liver disease (CLD) were screened for common viral etiologies and others serological markers of HBV. Amplification of surface, precore and polymerase genes of HBV was performed in patients negative for other etiologies. Genotyping and sequencing of the precore region was performed for OBI cases. Results: Twenty-nine (7.61%) cases of OBI were identifiedof which 9 had chronic liver disease (CHD), 11 liver cirrhosis (LC) and 9 hepatocellular carcinoma (HCC). Majority of OBI cases were detected by amplification of surface gene 26 (89.6%), followed by pre-core gene 12 (41.3%). Their liver functions tests were significantly deranged in comparison to overt HBV cases. IgG anti HBc was present in 8 (27.6%) OBI cases. Mutation was observed in 8 (32%) in pre-core region at nt. 1896 of overt HBV cases. Genotype D was the predominant genotype. In conclusion: OBI in our study was characterized by predominance of genotype D and more severe clinical and biochemical profile in comparison to overt HBV. IgG anti HBc positivity could be utilized as a marker of OBI. We recommend use of sensitive nested PCR for diagnosis of OBI, amplifying at least surface and precore gene.